2013
DOI: 10.1073/pnas.1318750111
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neural populations can guide behavior by integrating inputs linearly, independent of synchrony

Abstract: Neurons are sensitive to the relative timing of inputs, both because several inputs must coincide to reach spike threshold and because active dendritic mechanisms can amplify synchronous inputs. To determine if input synchrony can influence behavior, we trained mice to report activation of excitatory neurons in visual cortex using channelrhodopsin-2. We used light pulses that varied in duration from a few milliseconds to 100 ms and measured neuronal responses and animals' detection ability. We found detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 68 publications
4
87
0
Order By: Relevance
“…For example, simply introducing irregularity in the pulse trains (while keeping their overall frequency constant) yields more detectable percepts, perhaps because irregular spiking is more biomimetic than regular spiking (39; but see ref. 40 for counterevidence). A compelling example of how biomimetic patterning might modulate the efficiency of ICMS is provided by Kimmel and Moore (41), who delivered stimulation to the frontal eye fields (FEF) and showed that pulse trains whose frequency ramps up-thereby more closely mimicking the natural activation of FEF neurons-are more effective at evoking saccades than flat, decelerating, or randomly varying ones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, simply introducing irregularity in the pulse trains (while keeping their overall frequency constant) yields more detectable percepts, perhaps because irregular spiking is more biomimetic than regular spiking (39; but see ref. 40 for counterevidence). A compelling example of how biomimetic patterning might modulate the efficiency of ICMS is provided by Kimmel and Moore (41), who delivered stimulation to the frontal eye fields (FEF) and showed that pulse trains whose frequency ramps up-thereby more closely mimicking the natural activation of FEF neurons-are more effective at evoking saccades than flat, decelerating, or randomly varying ones.…”
Section: Discussionmentioning
confidence: 99%
“…This complements other approaches, including dynamical causal modeling, which tends to focus on more abstract, neural mass models (e.g., Kiebel et al , 2009; Moran et al , 2013), which may not reflect the biophysical properties critical to some neural computations. We focus, as invited, on brain rhythms, which reflect and influence spiking activity; however, dynamic processes can also happen in the absence of rhythmic brain activity (Ecker et al , 2010; Renart et al , 2010; Ainsworth et al , 2012; Histed & Maunsell, 2014) and the dynome includes other temporal structures as well (Larson-Prior et al , 2013). …”
Section: What Constitutes the Dynome?mentioning
confidence: 99%
“…Another recent paper using direct detection of brain stimulation, Histed and colleagues (2014), employed direct optogenetic drive of pyramidal neurons across neocortical layers in V1 [78 ]. Histed et al manipulated the synchronous output of visual cortex by comparing a high intensity, short duration versus lower intensity longer duration optogenetic stimuli, which the authors matched for the number of total action potentials generated.…”
Section: Optogenetic Drive Of Fs Interneurons Can Enhance Sensory Detmentioning
confidence: 99%
“…However, Lee et al (2012)also observed benefits to perception from FS activation in a regime they showed in other experiments should largely suppress pyramidal firing, suggesting that area-specific differences may not be a viable explanation. The discrepancy in the inferences drawn from these several studies and those ofHisted et al (2014) indicates that parallel experiments should be conducted that directly address this issue, ideally in the same laboratory or in close collaboration across the laboratories that came to distinct conclusions.…”
mentioning
confidence: 97%